(untitled) (PJDOL, 2023)
Socialization is in the process of personality formation. Successful socialization can result in uniformity within a society. If all learners receive the same socialization, it is likely that they will share the same beliefs and expectations. Socialization is the ability of learners to identify with community, communicate purposefully in a trusting environment, and develop inter-personal relationships by way of protecting their individual personalities.